2021
DOI: 10.1002/bsd2.160
|View full text |Cite
|
Sign up to set email alerts
|

Climate adaptation within the tourism sector of a small island developing state: A case study from the coastal accommodations subsector in the Bahamas

Abstract: Tourism in Small Island Developing States (SIDS) is vulnerable to climate change. Using the Bahamas as a case study, this study presents findings from a survey administered with property managers from the coastal accommodations sector to identify their adaptation strategies to tackle climate change. We also evaluate their adaptive capacity by developing SIDS‐specific indicators based on a capitals approach. Findings indicate that efforts toward adaptation were limited to disaster preparedness for hurricanes, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In the Indonesian context, the low disclosure of water use and management requires the company's internal structure, such as the board, to better understand the importance of this in dealing with climate change uncertainty. Another research from Pathak et al (2021) found that a lack of funds and knowledge will hinder access to information on climate change, so the proposed antecedents of voluntary pro‐environmental behavior are needed (Saifulina et al, 2021) as a basis for a willingness to develop sustainability. Weak corporate governance practices in emerging markets, coupled with a lack of strong legal and regulatory oversight from national institutions (Bahadori et al, 2021) support the fact that the presence or absence of diversity within boards does not influence the water information provided to the public due to of the lack of relevant legislation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Indonesian context, the low disclosure of water use and management requires the company's internal structure, such as the board, to better understand the importance of this in dealing with climate change uncertainty. Another research from Pathak et al (2021) found that a lack of funds and knowledge will hinder access to information on climate change, so the proposed antecedents of voluntary pro‐environmental behavior are needed (Saifulina et al, 2021) as a basis for a willingness to develop sustainability. Weak corporate governance practices in emerging markets, coupled with a lack of strong legal and regulatory oversight from national institutions (Bahadori et al, 2021) support the fact that the presence or absence of diversity within boards does not influence the water information provided to the public due to of the lack of relevant legislation.…”
Section: Methodsmentioning
confidence: 99%
“…In the Indonesian context, the low disclosure of water use and management requires the company's internal structure, such as the board, to better understand the importance of this in dealing with climate change uncertainty. Another research from Pathak et al (2021) found that a lack of funds and knowledge will hinder access to information on climate change, so the proposed antecedents of voluntary pro-environmental behavior are needed (Saifulina et al, 2021) emerging markets, coupled with a lack of strong legal and regulatory oversight from national institutions (Bahadori et al, 2021) support the fact that the presence or absence of diversity within boards does not influence the water information provided to the public due to of the lack of relevant legislation. The result of this study is also in line with prior research which found that gender diversity does not affect the application of quality management tools (Monteduro et al, 2011), profitability (Dobbin & Jung, 2011), and CSR (Yarram & Adapa, 2021), thus contradicting stakeholder theory.…”
Section: Bgd On Water Disclosurementioning
confidence: 99%